Sosialisasi Kemasyarakat Untuk Meningkatkan Minat Kewirausahaan Masa Pandemi Covid-10 Di Desa Mekarsari, Tambun, Bekasi - Siahaan , Matdio (Jurnal Pengabdian kepada Masyarakat UBJ, 2022)
This community service activity aims to build community independence in order to develop the potential of the surrounding environment, especially entrepreneurship programs in the midst of the COVID-19 pandemic. This community service activity method uses the lecture or counseling method, discussion and learning that is practiced by participants and resource persons. The lecture method is used to convey general knowledge about the development of entrepreneurial intentions for the people of Desa Mekarsari. Learning methods are used to transfer knowledge and skills possessed by resource persons to community members. This training involved lecturers from Bhayangkara University, Jakarta Raya, in collaboration with the residents of Mekarsari Village, Kec. Tambun Selatan, Kab. Bekasi as the target subject.